Digital Preachers and Authority: Reframing MUI’s Boycott Fatwa on YouTube - Rifqi Favian; Fahrizal Mahdi; Hanafi (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2026)
This study analyzes how the 2023 fatwa issued by the Indonesian Ulema Council (MUI) on boycotting Israeli-affiliated products is reframed by digital religious authorities on YouTube, using Fairclough's three-level model of Critical Discourse Analysis. Data include the fatwa text, video narrations by Buya Yahya, Guru Gembul, and audience comments on their channels. At the micro level, MUI's cautious legal language is later sharpened into explicit moral condemnation of Israel, while Buya Yahya emphasizes conscience-based affective language and Guru Gembul adopts a rational-strategic register questioning the boycott's effectiveness. At the meso level, these differences stem from contrasting institutional positions: pesantren-based authority versus non-institutional commentary. At the macro level, this produces divergent audiences, homogeneous and affirmative for Buya Yahya, polarized and critical for Guru Gembul. The study shows how a single fatwa fractures into competing digital religious publics, with authority increasingly shaped by rhetorical strategy rather than credentials alone.